Assessing Seismic Performance of Moment Resisting Frame and Frame-shear Wall System Using Seismic Fragility Curve. (2017) - Astriana, Linda; Sangadji, Senot; Purwanto, Edy; Kristiawan, S.A.
Abstract: Explosive population and economic development in the city has forced engineer to design and build more vertical buildings. In order to be resilient in earthquake prone region, these tall buildings have to achieve a specific level of performance under earthquake loading. A comprehensive methodology for assessing the seismic performance is required which can be attained by developing structural fragility function of the structure. Fragility curves is a probabilistic function relating damage level (engineering demand parameter) with intensity measure, i.e. spectral acceleration. This paper investigates the seismic performance of moment resisting frame as compared to frame-wall system of structures. The structural response of fully deterministic structural models was, then, analyzed employing nonlinear pushover analysis yielding capacity spectrums. For each capacity spectrum in every building system, the damage states were defined, whereas average inter-story drift values for each damage state were converted into corresponding amount of spectral acceleration leading to the development of fragility curves. The paper is concluded by carrying out evaluation of the damage state based on HAZUS-MH MR5 and ATC-40.